2000
DOI: 10.1163/156856200743670
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking and characterisation of gelatin matrices for biomedical applications

Abstract: Cross-linking of gelatin A and B with N,N-(3-dimethylaminopropyl)-N'-ethyl-carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) was optimised by varying the NHS/EDC molar ratio at constant EDC concentration. Native and cross-linked gelatin gels were characterised using the degree of swelling, the number of free amine groups, the phase transition temperature, and titration of the carboxylic acid residues. The cross-linking reaction was most efficient at a NHS to EDC molar ratio of 0.2. At higher NHS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
185
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(187 citation statements)
references
References 33 publications
1
185
0
1
Order By: Relevance
“…20,21 Hence biocompatible water soluble carbodiimide class cross linker EDC has also been tried, which is widely used for cross linking collagen in dermal tissue engineering. 22 EDC crosslink the amino groups of one polypeptide chain with the carboxylic groups of the adjacent polypeptide chain by forming the extra amide bond without its incorporation. 23,24 The presence of gelatin and PVP in GPE scaffolds was analyzed by FTIR spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Hence biocompatible water soluble carbodiimide class cross linker EDC has also been tried, which is widely used for cross linking collagen in dermal tissue engineering. 22 EDC crosslink the amino groups of one polypeptide chain with the carboxylic groups of the adjacent polypeptide chain by forming the extra amide bond without its incorporation. 23,24 The presence of gelatin and PVP in GPE scaffolds was analyzed by FTIR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…In this study gelatin/PVP IPN based scaffolds degrade faster than gelatin scaffolds (GPE > GPG = GE > GG). The fast degradation of EDC cross-linked sample could be due to the cross linking mechanism, 22 where EDC cross links amino and carboxylic groups of adjacent fgelatin molecules by forming new amide bond that in turn has increased possibility of hydrogen bonding with the water and other constituents of the storage media, leading to hydrolytic degradation. This study confirmed that the materials are degradable, but the degradation rate of these materials (in par with formation of new tissues) should be investigated in future through implantation studies.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of the microcarrier porosity in this study is unclear, but in a recent study we have investigated the impact of pore diameters on human chondrocyte proliferation (Pettersson et al, submitted). This type of gelatin microcarriers is cross-linked with a non-zero length diisocyanate cross-linking agent, through the reaction of free amine groups of lysine and hydroxylysine or free carboxylic acid residues of glutamic and aspartic acid of the protein molecules [Kuijpers et al, 2000]. Concerning in vitro degradation, Kong et al has reported continuous material release from this type of gelatin microcarrier in an in vitro system with a CHO cell line [Kong et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Printed imlants were crosslinked with EDC and intermediate products were stabilised with NHS in a ratio of 5:1 (EDC: NHS) that was described as most efficient in literature [4]. Three crosslinking methods were compared: insertion, dipping, spraying.…”
Section: Evaluation Of Crosslinking-methodsmentioning
confidence: 99%
“…In contrast to the often used aldehydes, the crosslinkers in this work -EDC and NHS -are generally known as zero-length crosslinker as they do not integrate new structures to the existing hydrogel-network, but link carboxylic acid groups with amine groups to new amide bonds within the gelatin [4].…”
Section: Evaluation Of Crosslinking-methodsmentioning
confidence: 99%